Predictive Value of the Baseline and Early Changes in Blood Eosinophils for Short-Term Mortality in Patients with Acute Respiratory Distress Syndrome - Peng J; Tang R; Qi D; Yu Q; Hu H; Tang W; He J; Wang D (Dove Medical Press, 2022)
Junnan Peng,* Rui Tang,* Di Qi, Qian Yu, Hao Hu, Wen Tang, Jing He, Daoxin Wang Department of Respiratory and Critical Care Medicine, Second Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Daoxin Wang; Jing He, Department of Respiratory and Critical Care Medicine, Second Affiliated Hospital of Chongqing Medical University, No. 76 Linjiang Road, Yuzhong District, Chongqing, 400010, People’s Republic of China, Email wangdaoxin0163@163.com; miss_hejing@126.comBackground: Eosinophils play an essential role in the pathogenesis of acute respiratory distress syndrome (ARDS). We aimed to assess the association between the baseline blood eosinophils, eosinophil changes during the first week in the intensive care unit (ICU) and short-term patient outcomes.Methods: All patients meeting the Berlin definition of ARDS from the Medical Information Mart for Intensive Care IV database were retrospectively analyzed. We used logistic regression, Kaplan–Meier survival and random forest analysis to determine the association between the baseline eosinophils and short-term mortality. Then the trends in eosinophils over time were compared between the survivors and non-survivors using a generalized additive mixed model (GAMM), which is a common approach used for analysis of repeated measurement data. Area under the receiver-operating characteristic curve (AUC) was used to evaluate the predictive value.Results: A total of 1685 patients were included, and the 30-day mortality was 25.1%. Kaplan–Meier analysis showed that patients with high baseline eosinophils (> 0.3%) had lower 30-day mortality (p < 0.001). Random forest model selected the baseline eosinophils as an important factor associated with 30-day mortality. Multivariable logistic regression analysis identified high baseline eosinophils as an independent factor for 30-day mortality (OR 0.743, 95% CI 0.568– 0.970). The GAMM result showed that the levels of eosinophils were increased in both survival and non-survival groups, and the between-group differences increased over time, with an average of 0.154 daily after adjusting for confounders. The AUC of changes in eosinophils within the first week was significantly higher than that of baseline eosinophils.Conclusion: There is a negative association between the baseline eosinophils and short-term mortality in ARDS patients, and the differences in eosinophils increased over time between the survivors and non-survivors. Higher increase in eosinophils is associated with decreased short-term mortality, and dynamic monitoring of eosinophils could better predict the survival of ARDS patients.Keywords: ARDS, eosinophils, 30-day mortality, generalized additive mixed model, change